An unusual cause of recurrent bloody tear - Tasneem F Alhaj; Vittal I Nayak; Karthik Sriprakash; Tarika K Perikal (Indian Journal of Ophthalmology, 2017)
We describe a female patient who presented with watering followed by swelling in the left infraorbital area of 5 years duration. She had previously been prescribed topical antibiotics on several occasions with no improvement. On pressure over the swelling, there was blood-tinged discharge from the left eye and nostril. Magnetic resonance imaging revealed an enhancing, well-defined mass lesion in the inferomedial aspect of the left orbit, likely of nasolacrimal origin. Computed tomography dacryocystogram with three-dimensional reconstruction showed a well-circumscribed mass with an irregular surface, originating from the lacrimal sac. Gram staining and potassium hydroxide mount from the regurgitant fluid revealed thick-walled cysts with sporangia suggestive of Rhinosporidium seeberi infection. Excision biopsy of the lesion confirmed R. seeberi as the causative agent. The patient has been put on long-term dapsone therapy to prevent a recurrence and has been asked to follow-up 6 months later.